FAKTOR â FAKTOR YANG MEMPENGARUHI KETERANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada SKPD di Kabupaten Sidoarjo) - Anggraeni, Dian Tri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to analyze (a) the influence of human resources quality to the reliability of local government financial reporting, (b) the influence of the utilization of information technology to the reliability of local government financial reporting, (c) the influence of accounting internal control system to the reliability of local government financial reporting, (d) the influence of financial supervision to the reliability of local government financial reporting. Quantitative method is used as the research method. The samples are 20 SKPD in Sidoarjo regency. The data is the primary data which have been obtained from questionnaires which are directly distributed to the respondents who are the head and the staffs of financial division on local work unit of Sidoarjo regency. 54 of 60 respondents can be put into data processing. Afterward the obtained data is analyzed by using Partial Least Square (PLS). The result of research shows that the quality of human resources and financial supervision has positive influence to the reliability of local government financial reporting. While the utilization of information technology and accounting internal control system has no information to the reliability of local government financial reporting. Keywords: Reliability, Local Government Financial Reporting, the Quality of Human Resources, Information Technology, Internal Control System, and Financial Supervision